2013
DOI: 10.1038/ng.2539
|View full text |Cite
|
Sign up to set email alerts
|

Reduced dosage of ERF causes complex craniosynostosis in humans and mice and links ERK1/2 signaling to regulation of osteogenesis

Abstract: The extracellular signal-related kinases 1 and 2 (ERK1/2) are key proteins mediating mitogen-activated protein kinase signaling downstream of RAS: phosphorylation of ERK1/2 leads to nuclear uptake and modulation of multiple targets. Here, we show that reduced dosage of ERF, which encodes an inhibitory ETS transcription factor directly bound by ERK1/2 (refs. 2,3,4,5,6,7), causes complex craniosynostosis (premature fusion of the cranial sutures) in humans and mice. Features of this newly recognized clinical diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
191
0
8

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(231 citation statements)
references
References 47 publications
22
191
0
8
Order By: Relevance
“…In contrast to the original report of a significant number of ERF mutations in multiple-suture craniosynostosis, we failed to detect a mutation in this gene. This study suggests that the frequency of ERF mutations may be lower than previously suggested (2-3%), 11 but analysis of larger cohorts are required to determine this further.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…In contrast to the original report of a significant number of ERF mutations in multiple-suture craniosynostosis, we failed to detect a mutation in this gene. This study suggests that the frequency of ERF mutations may be lower than previously suggested (2-3%), 11 but analysis of larger cohorts are required to determine this further.…”
Section: Discussionmentioning
confidence: 52%
“…29 During the course of the project, two novel craniosynostosis genes were identified; TCF12 (Sharma et al 9 ) and ERF. 11 We subsequently screened both genes in the 72 patients, which remained genetically undiagnosed after the cascade screening. Five patients were found to have a TCF12 variant, accounting for 2.7% of the total cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LOF variants in ERF cause multisuture craniosynostosis with variable midface hypoplasia (29). To our knowledge, no cases of isolated metopic NSC have previously been described in conjunction with LOF mutation in ERF.…”
Section: Variable Expressivity Of Mutations In Syndromic Craniosynostmentioning
confidence: 94%
“…In several mouse models, Apert FGFR2(S252W) mutations activate ERK1/2, p38 MAPK, AKT, β-catenin, and PLCγ in osteogenic cells, which may contribute to premature cranial ossification (Chen et al 2003;Kim et al 2003;Shukla et al 2007;Yin et al 2008;Wang et al 2010;Suzuki et al 2012). Interestingly, reduced dosage of ERF, an inhibitory ETS transcription factor directly bound by ERK1/2 signaling, was found to cause craniosynostosis in humans and mice, implying a role of ERF downstream from ERK signaling in cranial suture ossification (Twigg et al 2013). In human craniosynostosis, increased osteoblast gene expression and cranial osteogenesis induced by Apert FGFR2(S252W) mutation are related to PLCγ and PKCα activation (Lemonnier et al 2001b).…”
Section: Intracellular Pathways Involved In Craniosynostosismentioning
confidence: 99%